Facile Synthesis of Crystalline Polymeric Carbon Nitrides with an Enhanced Photocatalytic Performance under Visible Light. Issue 18 (25th March 2015) - Liang, Qinghua; Huang, Zheng‐Hong; Kang, Feiyu; Yang, Quan‐Hong
Abstract Poly(triazine imides) intercalated with Li+ and X− (PTI/X, X=Cl or Br), which are described widely as crystalline polymeric carbon nitrides, were synthesized in a facile manner by heating a mixture of melamine and LiX. This method has the advantages of low cost, scalable production, and high efficiency. Importantly, both PTI/Cl and PTI/Br exhibit an enhanced photocatalytic performance compared to conventional graphitic polymeric carbon nitride in the degradation of rhodamine B under visible‐light irradiation because of their higher visible‐light‐harvesting ability and charge carrier separation efficiency.